Estimation of the additional costs of chemotherapy for patients with advanced non-small cell lung cancer. Issue 7 (1st July 2005) - Maslove, L; Gower, N; Spiro, S; Rudd, R; Stephens, R; West, P
Abstract : Background: A large multicentre randomised trial, the Big Lung Trial, which in part compared supportive care with or without cisplatin-based chemotherapy in patients with advanced non-small cell lung cancer, provided an opportunity to evaluate the impact on the UK National Health Service of the costs incurred with the use of chemotherapy. Methods: This costing study was based on the retrospective collection of resource use data from hospital records. Case notes from 194 patients (98 chemotherapy + supportive care (C), 96 supportive care alone (NoC)) were inspected in eight centres recruiting the largest numbers of patients into the Big Lung Trial. Quantities were multiplied by fixed unit costs to calculate a total cost for each patient. The main outcome measure was the total cost incurred by the use of secondary care resources (including investigations, chemotherapy, radiotherapy, surgical procedures, inpatient days, outpatient attendances, and hospice inpatient care) in the two groups. Results: Patients randomised to receive cisplatin-based chemotherapy had an average of 3.4 more inpatient bed days than the mean of 11.9 days for patients randomised to supportive care alone, and more outpatient attendances. NoC patients were more likely to have received palliative radiotherapy. The mean total cost for C patients was £5355 compared with £3595 for the NoC group, difference £1760 (95% CI £781 to £2742). When split, the cost in the C group associated with the administration of chemotherapy was £1233 and non-chemotherapy costs were £4122. Conclusion: The additional cost of chemotherapy was not offset by a reduction in subsequent costs (as the non-chemotherapy costs were similar), so the survival benefit of about 10 weeks observed in the C group was achieved with the cost of chemotherapy administration.